RESEARCH ON THE EFFICIENCY OF USE OF NATURAL POLYMER FLOCCULANTS IN THE PROCESS OF WATER SOLUTION PURIFICATION - Solodovnik, Tetyana Volodymyrivna; Kultenko, Valentyna Serhiivna; Slis, Andrii Anatoliiovych (Вісник Черкаського державного технологічного університету, 2020)
Natural flocculants are studied in the processes of water solution purification using the method of Jar-test. Experimental part of the work involves the research of different flocculants for the purification of colored water. The aim of this study is to determine the efficacy and optimal doses of flocculants in combination with aluminum sulfate. The flocculants such as chitosan, sodium alginate, starch and polyacrylamide are used for researching. As a coagulant, Al2(SO4)3·18H2O with a concentration of 10 % is used. It has been established that chitosan is the most effective flocculation reagent. It is explored that such factors as the dosage of reagents, chemical nature of links and the composition of polymer macromolecules, physical and chemical parameters of the process and the concentration of reagents influence the flocculation process. The optimal conditions for carrying out the process of flocculation are established